(untitled) (European Bison Conservation Newsletter, 2012)
The restitution of European bison to the Ukrainian Eastern Carpathians has been conducted since 1965. In the early 1990s, the bison numbers reached their peak i.e. about 270 individuals. Three bison sub-populations (Maydan, Nadvirna, Bukovyna) existed then. By the 1990s, the bison numbers had declined considerably. The last bison of the Nadvirna sub-population were recorded in the late 1990s; the last animals of the Maydan sub-population died, probably, during the winter of 2008–2009; the number of animals in the Bukovyna sub-population is constantly decreasing. Present numbers of European bison in the Eastern Carpathians are slightly over 40 individuals, which makes necessary to introduce appropriate conservation measures towards an increase of bison numbers in this region. This task requires the implementation of following program: (1) the establishment of breeding stations within area of Skolyvski Beskydy National Nature Park and Vyzhnytsya National Nature Park; (2) introduction of animals from the Uladiv sub-population (Ukraine), Belarus, Poland, Russia, and other European countries for the purpose of establishing viable bison herds in the newly created breeding stations; (3) identification of habitats suitable for e. bison in the Eastern Carpathians within Ivano-Frankivsk region; (4) supplementation with new animals the sub-population of Bukovyna.